A Comparative Analysis of Effects of Education on Sub-Saharan Africa’s Economic Growth - Wilfred, Akinola Gbenga; Bokana, Gerry Koye (Journal of Economics and Behavioral Studies, 2017)
This study aims to analyze and to compare the effects of various levels of education on the economic growth of some selected countries in Sub-Saharan Africa (SSA) between 1980 and 2015.It is hypothesized in the study that various levels of education have significant positive impacts on the economic growth of some selected sub-Saharan Africa countries over the stated period. Fixed effect Least Square Dummy Variable (LSDV) and a robust version of System Generalized Methods of Moment (SYSGMM) are adopted as model estimating techniques. Results from the LSDV model indicate increasing positive impacts of various levels of education on the economic growth of the thirty selected SSA countries. This trend of significance is corrected in the dynamic model, but with negative effects on the lower levels of education on growth while higher education output which negatively impacted on growth is reversed. The study systematically compares the effects of education on growth when higher education is included and when it is excluded both at the enrolment and output level in the regression model. We found different results at each instance for the various levels. Therefore, the major conclusion of this study is that higher education human capital at the output level appears to be the most significant of all the levels of education. However, this advantage enjoyed by higher education could have been as a result of cumulative effects from other levels of education over time. We, therefore, conclude that higher education should be supported with strong education policy implementation, as this could have a positive impact on SSA economic growth.